ПИЩЕВЫЕ И БИОЛОГИЧЕСКИ АКТИВНЫЕ ДОБАВКИ, ИСПОЛЬЗУЕМЫЕ ПРИ ПРОИЗВОДСТВЕ ВОДКИ ОСОБОЙ (Experimental biology, 2015)
In this article the food and biologically active additives used by manufacture vodka the special are considered. And, also, their influence on a human body is considered. Given article is actual for today as both modernmanufacturers, and modern consumers are rather interested in it.
Keywords: manufacture vodka